U–Pb dating of detrital zircon from Permian successions of the South Kitakami Belt, Northeast Japan: Clues to the paleogeography of the belt. (23rd December 2021) - Li, Yuxiao; Takeuchi, Makoto
Abstract: The South Kitakami Belt in the northeast Japan is unique in presence of a thick Paleozoic–Mesozoic sedimentary rocks. The Permian sedimentary succession in the Maiya area of this belt is divided into the Nishikori, Tenjinnoki, and Toyoma formations, in ascending stratigraphic order. The Tenjinnoki Formation includes the Yamazaki Conglomerate Member containing granitic clasts. We performed U–Pb dating for detrital zircon of one sample of tuffaceous sandstone from the Nishikori Formation, six samples of sandstone from the Tenjinnoki and Toyoma formations, and five granitic clasts from the Yamazaki Conglomerate using laser ablation‐inductively coupled plasma‐mass spectrometry. Our dating results show that the tuffaceous sandstone sample has two age peaks at 287 and 301 Ma for the Nishikori Formation, three age peaks at 320–300, 290, and 270 Ma for the Tenjinnoki and Toyoma Formation, and ages of 311, 300, and 270 Ma from granitic clasts of the Yamazaki Conglomerate. In addition, older ages of 452–435 and 380 Ma were obtained from some zircon grains of the sandstone and granitic clasts. Our results suggest igneous activity in these periods. The South Kitakami Belt's origin with respect to continental blocks has been discussed in regard of the margin of North China Block or South China Block. Based on the stratigraphic ages and timing of igneous activity, we conclude that during the Permian the South Kitakami Belt was located at the margin of the South Central Asian Orogenic Belt, near the Solonker‐Xra Moron‐Changchun suture and the North China Block in East Asia.